Genomic and biological insights of bacteriophages JNUWH1 and JNUWD in the arms race against bacterial resistance - Zhang, Hengwei; You, Jiajia; Pan, Xuewei; Hu, Yanglu; Zhang, Zan; Zhang, Xian; Zhang, Weiguo; Rao, Zhiming (Frontiers in Microbiology, 2024)
The coevolution of bacteria and bacteriophages has created a great diversity of mechanisms by which bacteria fight phage infection, and an equivalent diversity of mechanisms by which phages subvert bacterial immunity. Effective and continuous evolution by phages is necessary to deal with coevolving bacteria. In this study, to better understand the connection between phage genes and host range, we examine the isolation and genomic characterization of two bacteriophages, JNUWH1 and JNUWD, capable of infecting Escherichia coli. Sourced from factory fermentation pollutants, these phages were classified within the Siphoviridae family through TEM and comparative genomic analysis. Notably, the phages exhibited a viral burst size of 500 and 1000 PFU/cell, with latent periods of 15 and 20 minutes, respectively. They displayed stability over a pH range of 5 to 10, with optimal activity at 37℃. The complete genomes of JNUWH1 and JNUWD were 44,785 bp and 43,818 bp, respectively. Phylogenetic analysis revealed their close genetic relationship to each other. Antibacterial assays demonstrated the phages' ability to inhibit E. coli growth for up to 24 hours. Finally, through laboratory-driven adaptive evolution, we successfully identified strains for both JNUWH1 and JNUWD with mutations in receptors specifically targeting lipopolysaccharides (LPS) and the lptD gene. Overall, these phages hold promise as additives in fermentation products to counter E. coli, offering potential solutions in the context of evolving bacterial resistance.